2019
DOI: 10.1002/lno.11368
|View full text |Cite
|
Sign up to set email alerts
|

Response of the sea‐ice diatomFragilariopsis cylindrusto simulated polar night darkness and return to light

Abstract: Arctic photoautotrophic communities must survive through polar night darkness until light returns in spring. We tracked changes in the cellular resource allocations and functional capacities of a polar sea-ice diatom, Fragilariopsis cylindrus, to understand acclimation processes in both darkness and during the subsequent return to light. We measured parameters at specific time-points over 3 months of darkness, and then over 6 d after a return to light. Measured parameters included cell number and size, cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 83 publications
4
34
0
Order By: Relevance
“…Nymark et al (2013, and references therein) have previously reported that Phaeodactylum tricornutum cells complete an ongoing cell cycle when placed in the dark. Morin et al (2019) and Lacour et al (2019) made the same observation with Fragilariopsis cylindrus and Chaetoceros neogracilis, respectively. The total cell concentration then remained stable until the end of DA but after 30 d in the dark, the abundance of P1 cells began slowly to decrease while P2 and P3 populations began to emerge (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Nymark et al (2013, and references therein) have previously reported that Phaeodactylum tricornutum cells complete an ongoing cell cycle when placed in the dark. Morin et al (2019) and Lacour et al (2019) made the same observation with Fragilariopsis cylindrus and Chaetoceros neogracilis, respectively. The total cell concentration then remained stable until the end of DA but after 30 d in the dark, the abundance of P1 cells began slowly to decrease while P2 and P3 populations began to emerge (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Among the small flagellated cells, two species that periodically dominate phytoplankton assemblages in Arctic waters were found throughout the Polar night: Micromonas polaris and Phaeocystis pouchetii (Vader et al, 2015). Natural microalgal assemblages, and in particular diatoms, are able to survive extended periods of darkness from months to years (Zhang et al, 1998;McMinn and Martin, 2013), while retaining their ability to resume physiological activity quickly once light returns (Kvernvik et al, 2018;Lacour et al, 2019;Morin et al, 2020). Diatoms also seem to retain their photophysiological characteristics during extended periods of darkness relatively unchanged as compared to flagellates, which possibly enables them to utilize the returning light in early spring very efficiently (van de Poll et al, 2020).…”
Section: Diversity Of Under-ice Blooms: Phenology Strategy Assemblamentioning
confidence: 99%
“…Measurements and experiments during the polar night in Svalbard indicate that phytoplankton are capable to reinitiate photosynthesis almost immediately upon reillumination in the laboratory, even if in situ primary production is not measurable (Berge et al 2015;Kvernvik et al 2018). From experiments with single strains of polar phytoplankton, there is increasing evidence that species differ in the extent to which they manage to decrease metabolic energy needs in the dark as well as in their capacity to reestablish photosynthesis and growth upon re-illumination, yet overall capacities for recovery are remarkable (Kennedy et al 2019;Lacour et al 2019;Morin et al 2019;van de Poll et al 2020a). In view of this, it seems to be the return of sufficient sunlight (Cohen et al 2020) for net growth rather than germination cues or molecular clocks that determines the start of phototrophic production.…”
mentioning
confidence: 99%